The Lucifer-Effect – The Importance of Arendt’s ’Banality of Evil’ for Social Psychology - H., W. (HannahArendt.net, 2012)
In 1971 the social-psychologist Philip Zimbardo showed with his ”Stanford Prison Experiment“ that certain social and political conditions are favourable for the emergence of the ”banality of evil“ (see the film The Experiment, 2001, by Oliver Hirschbiegel).